Species and forms of Dictyophora (Fungi, Basidiomycetes, Phallales) in Mexico and observations on their distribution in Latin America - Guzmán, Gastón; Montoya, Leticia; Bandala, Victor M. (Instituto de Ecología, A.C., 1990)
A study of the genus Dictyophora is presented, providing a key to the Mexican species and forms, as well as their distributional analysis in the country (through 10 States), and observations on the presence of the genus in Guatemala, Costa Rica and Brazil. In conclusión D. duplicata (Bosc) Fischer is distributed in damp températe regions and in North America, while the 3 forms of D. indusiata (Vent.: Pers.) Desv. [D. indusiata f. indusiata, D. indusiata f . lutea (Liou & Hwang) Kobayasi and D. indusiata f. rosea (Cesati) Kobayasi] are widespread in tropical and subtropical regions.